Digital Transformation in Education and Training in Vietnam - Van, Truong Hoang Thuy (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Digital transformation in Education and Training is an issue of concern in many countries. The explosion in information technology creates non-traditional training methods, vigorously promoting the development of profoundly transformative education for people. Digital transformation has contributed to improving the quality of management, teaching, and learning, an important factor for the education sector, and significantly impacts society in the immediate and long term. Therefore, Vietnam in general and the education and training sector in particular must urgently implement digital transformation requirements to take advantage of the opportunities the 4th Industrial Revolution brings. Through the actual situation, the article analyzes and evaluates the current situation, proposing solutions to complete digital transformation in the field of education and training in Vietnam today.